2020
DOI: 10.1177/1054137320906405
|View full text |Cite
|
Sign up to set email alerts
|

Instagram’s Affordances and the Visual Construction of Solidarity after a Mass Shooting

Abstract: Solidarity is a common response after a mass shooting. Social media and social media affordances, such as hashtags, are valuable technological tools after such events. How does social media facilitate the response to mass shootings? In particular, how do platform affordances shape solidarity practices? To this end, I analyzed Instagram images tagged #LafayetteStrong 2 years after a mass shooting in Lafayette, Louisiana. I observed several solidarity-inspired themes including material objects, community events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Typically expressed by artistic illustrations, memes, and hashtags, solidarity symbols utilise the affordances and fluidity of digital spaces. They serve as tools of mourning (Mielczarek, 2018), bonding icons (Harju, 2019), and visual expressions of solidarity used to mobilise collective support (Pearce, 2020). Not restricted to violent death, solidarity symbols also emerge in the context of other tragedies where death is unexpected.…”
Section: Introductionmentioning
confidence: 99%
“…Typically expressed by artistic illustrations, memes, and hashtags, solidarity symbols utilise the affordances and fluidity of digital spaces. They serve as tools of mourning (Mielczarek, 2018), bonding icons (Harju, 2019), and visual expressions of solidarity used to mobilise collective support (Pearce, 2020). Not restricted to violent death, solidarity symbols also emerge in the context of other tragedies where death is unexpected.…”
Section: Introductionmentioning
confidence: 99%
“…Instagram also affords users the opportunity to connect with other users around the globe using features, such as likes, comments, direct messages, and hashtags. Hashtags, in particular, have demonstrated utility in creating solidarity and collectivity during the aftermath of mass shootings (Pearce, 2020). For example, prior research indicated that Instagram users utilized the #LafayetteStrong hashtag after a mass shooting at the Grand Theater in Lafayette, Louisiana as a way to confirm and reinforce a community's local solidarity (Pearce, 2020).…”
mentioning
confidence: 99%
“…Hashtags, in particular, have demonstrated utility in creating solidarity and collectivity during the aftermath of mass shootings (Pearce, 2020). For example, prior research indicated that Instagram users utilized the #LafayetteStrong hashtag after a mass shooting at the Grand Theater in Lafayette, Louisiana as a way to confirm and reinforce a community's local solidarity (Pearce, 2020). These hashtag communities may also play a role in the discourse and the connections that are made between Instagram users who may be diagnosed with chronic illnesses, such as triple negative breast cancer.…”
mentioning
confidence: 99%